INNOVATIVE TECHNOLOGIES IN THE QUALITY OF EDUCATIONAL PROCESSES (SCIENCE TIME JOURNAL, 2026)
The integration of innovative technologies into education has become a defining feature of modern teaching and learning. These technologies play a crucial role in enhancing the quality of educational processes by improving accessibility, engagement, personalization, and efficiency. Digital tools such as artificial intelligence, learning management systems, virtual classrooms, and multimedia resources have transformed traditional pedagogical approaches. However, the effective use of these technologies requires proper infrastructure, teacher training, and methodological adaptation. This article examines the role of innovative technologies in improving educational quality, highlighting their benefits, challenges, and implications for future educational development. The study emphasizes the need for a balanced and strategic approach to technology integration in order to maximize its positive impact oneducation.